Sistem pendukung keputusan penerima program bedah rumah di desa maliwowo menggunakan metode simple additive weighting (SAW) - AMS, Asril; Paembonan, Solmin; Abduh, Hisma (Computer Science and Information Technology, 2023)
The aim of this research is to design and build a decision support system (DSS) for recipients of the house renovation program to help determine potential recipients of the house renovation program in Maliwowo Village more effectively and efficiently. This system uses a simple additive weighting (SAW) decision support system method. The system created was designed using the development of Unifed Modeling Language (UML) which consists of use case diagrams, activity diagrams and sequence diagrams. The software used in designing this system uses the PHP programming language, Laravel framework, XAMPP as the web server, PHPMySQL as the database. This research produces a decision support system consisting of various features that can be used to determine recipients of a home surgery program where data management can only be done by admins and officers. From the results of the Likert scale interval percentage questionnaire calculations in this study, respondents strongly agreed with this system.